Investigating peer and sorting effects within an adaptive multiplex network model - Francesca Lipari; Massimo Stella; Alberto Antonioni (Games, 2019)
Individuals have a strong tendency to coordinate with all their neighbors on social and economics networks. Coordination is often influenced by intrinsic preferences among the available options, which drive people to associate with similar peers, i.e., homophily. Many studies reported that behind coordination game equilibria there is the individuals' heterogeneity of preferences and that such heterogeneity is given a priori. We introduce a new mechanism which allows us to analyze the issue of heterogeneity from a cultural evolutionary point of view. Our framework considers agents interacting on a multiplex network who deal with coordination issues using social learning and payoff-driven dynamics. Agents form their heterogeneous preference through learning on one layer and they play a pure coordination game on the other layer. People learn from their peers that coordination is good and they also learn how to reach it either by conformism behavior or sorting strategy. We find that the presence of the social learning mechanism explains the rising and the endurance of a segregated society when members are diverse. Knowing how culture affects the ability to coordinate is useful for understanding how to reach social welfare in a diverse society.
Keywords: C22; C73; D83; D85; Z13; 330; diffusion processes; coordination games; learning; multiplex network; cultural economics